Comparison of different polishing methods on the surface roughness of microhybrid, microfill, and nanofill composite resins - Moda, Mariana D. [UNESP]; Godas, Andre Gustavo de L. [UNESP]; Fernandes, Juliana C. [UNESP]; Suzuki, Thais Y. U. [UNESP]; Guedes, Ana Paula A. [UNESP]; Briso, André Luiz Fraga [UNESP]; Bedran-Russo, Ana Karina; Santos, Paulo Henrique dos [UNESP] (Wiley-Blackwell, 2018)
Aim: The aim of the present study was to evaluate the effect of different polishing methods on the surface roughness of resin-based composites subjected to a thermocycling procedure. Methods: A total of 192 specimens were divided into 24 groups, according to composite materials (Filtek Z250, Point 4, Renamel Nanofill, Filtek Supreme Plus, Renamel Microfill, and Premise) and finishing and polishing systems (Sof-Lex Pop On, Super Snap, Flexidisc, and Flexidisc+Enamelize). The specimens were subjected to thermocycling (5000 cycles). Results: Filtek Supreme Plus showed the lowest surface roughness values before thermocycling. After thermocycling, Filtek Supreme Plus continued to have the lowest surface roughness, with a statistically-significant difference for the other materials. After thermocycling, there was no statistically-significant difference among all the polishing techniques studied. Conclusions: The thermocycling was concluded as being able to change composite resins' surface roughness, whereas different finishing and polishing methods did not result in surface roughness changes after thermocycling.
Keywords: composite resin; polishing method; surface roughness; surface smoothness; thermocycling